2013
DOI: 10.1158/0008-5472.can-12-4258
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Sonic Hedgehog-Associated Medulloblastoma through Inhibition of Aurora and Polo-like Kinases

Abstract: Medulloblastoma (MB) is the most common malignant brain tumor in children. While aggressive surgery, radiation, and chemotherapy have improved outcomes, survivors suffer severe long-term side effects, and many patients still succumb to their disease. For patients whose tumors are driven by mutations in the Sonic hedgehog (SHH) pathway, SHH antagonists offer some hope. However, many SHH-associated MBs do not respond to these drugs, and those that do may develop resistance. Therefore, more effective treatment st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 55 publications
1
42
0
Order By: Relevance
“…Examples of second-site SMOis include the antifungal agent itraconazole and the cyclopamine derivative IPI-926 (saridegib), both of which have shown promise in preclinical studies (65,66). Inhibitors of downstream components of the SHH pathway include arsenic trioxide, which can promote GLI2 degradation (65); bromodomain inhibitors, which not only reduce expression and transcriptional activity of the SHH target MYCN (67) but also impair the function of GLI1 and GLI2 (68); and Aurora kinase A inhibitors, some of which can impair cell cycle progression as well as destabilize MYCN (69)(70)(71). The observation of increased PI3K pathway activity in tumors that develop resistance to SMOis (63,64), along with reports of recurrent mutations affecting this pathway (12,42), has suggested that PI3K inhibition may be an important strategy for preventing or overcoming resistance of SHH-MB.…”
Section: Shh Subgroupmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples of second-site SMOis include the antifungal agent itraconazole and the cyclopamine derivative IPI-926 (saridegib), both of which have shown promise in preclinical studies (65,66). Inhibitors of downstream components of the SHH pathway include arsenic trioxide, which can promote GLI2 degradation (65); bromodomain inhibitors, which not only reduce expression and transcriptional activity of the SHH target MYCN (67) but also impair the function of GLI1 and GLI2 (68); and Aurora kinase A inhibitors, some of which can impair cell cycle progression as well as destabilize MYCN (69)(70)(71). The observation of increased PI3K pathway activity in tumors that develop resistance to SMOis (63,64), along with reports of recurrent mutations affecting this pathway (12,42), has suggested that PI3K inhibition may be an important strategy for preventing or overcoming resistance of SHH-MB.…”
Section: Shh Subgroupmentioning
confidence: 99%
“…The observation of increased PI3K pathway activity in tumors that develop resistance to SMOis (63,64), along with reports of recurrent mutations affecting this pathway (12,42), has suggested that PI3K inhibition may be an important strategy for preventing or overcoming resistance of SHH-MB. Finally, preclinical studies have suggested that Polo-like kinase inhibitors may be particularly effective in SHH-MB (71,72). The heterogeneity of driver mutations and resistance mechanisms even within the SHH-MB subgroup suggests that careful patient selection and a diversity of therapeutic approaches will be necessary to effectively target this disease.…”
Section: Shh Subgroupmentioning
confidence: 99%
“…Due to radiation resistance, radiotherapy is sometimes ineffective, resulting in worse side effects (18). Therefore, it is necessary to understand the radiosensitive tumor targets and mechanisms underlying the development of radioresistance.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14] BI2536 is an ATP-competitive Plk1 kinase inhibitor and has been used in phase II clinical studies in breast cancer, endometrial cancer, head and neck cancer, melanoma, ovarian cancer and sarcoma. 15 In prostate cancer, Plk1 knockdown by RNAi causes induction of mitotic catastrophe, 16 suggesting that Plk1 might be a target and BI2536 might be a potential drug of PCa treatment.…”
Section: Introductionmentioning
confidence: 99%